To care in health: satisfaction with body image and self-esteem of old people - Chaim, Janice; Izzo, Helena; Tiemi Nakagawa Sera, Celisa (O Mundo da Saúde, 2009)
This study aims to investigate the relationship between satisfaction with body image and self-esteem of old people assisted by the Service of Geriatrics of Hospital of Clinics of Medical College of University of São Paulo (HCFMUSP), participants of the Group of Ambulatory Multidisciplinary Assistance to Old People (GAMIA) and the Physiotherapy Clinic for Very Old People (AFIL) in the year 2008, by knowing the impact of these aspects on health care of old people. We used an identification questionnaire; Body Mass Index (IMC); Sorensen and Stunkard Scale for self-evaluation of body image; Rosenberg’s Self-Esteem Scale (the version translated and adapted for Portuguese: DINI, 2001). Statistical Analysis: Fisher’s exact test; Kruskal- Wallis or t-Student test; variance analysis; p ≤0,05. In AFIL (n=11), all old people are women, average age 82.9 years (±3,5). In GAMIA (n=30), 50% of the participants are female and 50% male, average age 70.5 (±5,8). Averages of IMC indicated eutrophy: 27.33 AFIL= ±3.96; 26.71 GAMIA = ±5.16. Regarding satisfaction with body image, in AFIL, 27.27% were satisfied and 72.72% were not; in GAMIA, 43.44% were satisfied and 56.67% were not. As concerns Self-Esteem, the average of AFIL was 9.91 (±6.14) and GAMIA’s, 7.3 (±4.37), indicating a high Self-Esteem. No significant difference was observed between the groups. The evaluated data suggest that most old people is not satisfied with body image, and therefore would like to have leaner silhouettes than hey, although eutrophic. One may infer that they have a high Self-Esteem, even those displeased with their body image. It is known that satisfaction with body image and Self-Esteem depend on multiple factors and that they affect directly or indirectly cares with health of old people, deserving thus being addressed in future studies.